1994
DOI: 10.1016/0014-5793(94)00627-x
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Mn(II) in the catalysis of laccase, manganese peroxidase and lignin peroxidase from Phlebia radiata

Abstract: Oxidation capacities of laccase, manganese peroxidase (MnP) and lignin peroxidase (LIP) from Phlebia radiata were compared using non-phenolic (veratryl alcohol and ABTS) and phenolic (syringaldazine, vanillalacetone and Phenol red) compounds as reducing substrates. The effect of Mn(I1) on enzyme reactions was also studied. Highest specific activities were recorded with lactase in the oxidation of phenolic compounds or ABTS and irrespective of Mn(I1) concentration. LiP and MnP oxidized all these substrates but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Pyrolysis–GC/MS analysis demonstrated decrease in the amount of spruce wood phenylpropane units with concomitant increase in the number of smaller fragmented products from these lignin units, suggesting that especially the upregulated lignin peroxidases were actively attacking and converting the predominant non-phenolic structures of the spruce wood coniferous lignin. Lignin peroxidase LiP3 of P. radiata is an efficient oxidizer and degrader of non-phenolic lignin β-O-4 dimeric structures [30, 55]. P. radiata short-MnP3 is active against phenolic lignin compounds [29] and in decomposition of pine wood lignin [28].…”
Section: Discussionmentioning
confidence: 99%
“…Pyrolysis–GC/MS analysis demonstrated decrease in the amount of spruce wood phenylpropane units with concomitant increase in the number of smaller fragmented products from these lignin units, suggesting that especially the upregulated lignin peroxidases were actively attacking and converting the predominant non-phenolic structures of the spruce wood coniferous lignin. Lignin peroxidase LiP3 of P. radiata is an efficient oxidizer and degrader of non-phenolic lignin β-O-4 dimeric structures [30, 55]. P. radiata short-MnP3 is active against phenolic lignin compounds [29] and in decomposition of pine wood lignin [28].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, MnP activity is produced in the form of several isoenzymes [7][8][9][10], a phenomenon also observed in the case of the ligninolytic enzymes lignin peroxidase and laccase [1,2]. The significance of this multiplicity is not well understood, although in Phanerochaete chrysosporium it has been shown that the MnP isoenzymes are differentially regulated in response to nutrient limitation and culture age [11].…”
Section: Introductionmentioning
confidence: 99%
“…Phenerochaetae chrysosporium has not been reported to produce laccase, although other selective degraders of wood produces a combination of MnP and laccase like, Pleurotus ostreatus (Giardina et al, 1996), Pleurotus eryngii (Muñoz et al, 1997) and Dichomitus squalens (Périé et al, 1998) and a combination of MnP, LiP and laccase by Phlebia radiata (Lundell and Hatakka, 1994) or only laccase by Pycnoporus cinnabarinus (Eggert et al, 1996b). P. radiata produces at least 3 LiPs, 3 MnPs and one laccase (Moilanen et al, 1996).…”
Section: Discussionmentioning
confidence: 99%